Technical and Structural Innovations to European Transport in 21’1 Century - Tietze, Wolf; Steinmann-Tietze, Marie-Luise (Promet - Traffic&Transportation, 2012)
The aim of this study is to draw attention to the developmentopportunities presented to the population of Europe andbeyond, on the threshold of the 2JS1 centwy, resulting from thenew geopolitical situation and available technical innovations,plus the necessary decision-making required in the field oftransport politics. With the introduction of the unitary money,the Euro, giving further definition to the continental economicregion, new needs arise demanding an appropriate transportsystem. For this a Europe-wide Maglev net is essential. It musttake over quickly an increasing part of the traffic now carried inpart by road, in part by the conventional railway, in part by air.It appears wise to consider critically and to amend the generallyuncoordinated and partial renewals of the old system from thepoint of view of a continental-wide future, and with reference tothe superior ecological and economic advantages of moderntechniques coming to fruition in the Transrapid system. Theconsequences for future settlement structures and site evaluationare demonstrated by examples. The contrasts between thesystems should be clear in the comparative table of data (Table1). In addition, basic technical and political considerations arepresented by vGiious European experts in the booklet’Transrapid-Verkehr in Europa’ [1].